The Southern Ocean as a constraint to reduce uncertainty in future ocean carbon sinks - A. Kessler; J. Tjiputra (Earth System Dynamics, 2016)
Earth system model (ESM) simulations exhibit large biases compares to observation-based estimates of the present ocean CO2 sink. The inter-model spread in projections increases nearly 2-fold by the end of the 21st century and therefore contributes significantly to the uncertainty of future climate projections. In this study, the Southern Ocean (SO) is shown to be one of the hot-spot regions for future uptake of anthropogenic CO2, characterized by both the solubility pump and biologically mediated carbon drawdown in the spring and summer. We show, by analyzing a suite of fully interactive ESMs simulations from the Coupled Model Intercomparison Project phase 5 (CMIP5) over the 21st century under the high-CO2 Representative Concentration Pathway (RCP) 8.5 scenario, that the SO is the only region where the atmospheric CO2 uptake rate continues to increase toward the end of the 21st century. Furthermore, our study discovers a strong inter-model link between the contemporary CO2 uptake in the Southern Ocean and the projected global cumulated uptake over the 21st century. This strong correlation suggests that models with low (high) carbon uptake rate in the contemporary SO tend to simulate low (high) uptake rate in the future. Nevertheless, our analysis also shows that none of the models fully capture the observed biophysical mechanisms governing the CO2 fluxes in the SO. The inter-model spread for the contemporary CO2 uptake in the Southern Ocean is attributed to the variations in the simulated seasonal cycle of surface pCO2. Two groups of model behavior have been identified. The first one simulates anomalously strong SO carbon uptake, generally due to both too strong a net primary production and too low a surface pCO2 in December–January. The second group simulates an opposite CO2 flux seasonal phase, which is driven mainly by the bias in the sea surface temperature variability. We show that these biases are persistent throughout the 21st century, which highlights the urgent need for a sustained and comprehensive biogeochemical monitoring system in the Southern Ocean to better constrain key processes represented in current model systems.